Nanoparticles Formulated from Young Areca Nut Extract Utilizing Sodium Alginate as a Polymer and Calcium Chloride (CaCl2) - Rohmahdana, Indis Hilwa; Maharini, Indri; Purba, Eka Novita Br; Salsabilah, Indah; Nugroho, Aulia Hafizhah; Virginia, Yulwilla (Department of Chemistry, Faculty of Science and Technology Universitas Jambi, 2024)
Nanoparticles are an innovative formulation designed to enhance the bioavailability of drugs with poor absorption while allowing for a more targeted release of active compounds to minimize the risk of side effects. This study aims to develop nanoparticle formulations of young areca nut extract. The ionic gelation method, utilizing 0.02% CaCl2 and 0.1% sodium alginate, was employed in the preparation process. The three formulas were developed with different concentrations and volumes of extract. The evaluation of nanoparticles included phytochemical screening, particle size analysis (PSA), zeta potential, % transmittance, and FTIR for functional group identification. The characterization results of the nanoparticles from young areca nut seed ethanol extract showed that formulas F1, F2, and F3 had particle sizes of 84.267±1.250 nm, 97.367±1.079 nm, and 82.333±0.723 nm, respectively. The polydispersity index values ranged from 0.254±0.046 to 0.325±0.02, suggesting good particle distribution. The zeta potential values, all below -30 mV, indicate the stability of the colloidal suspension system. FTIR analysis showed that the young areca nut seed extract nanoparticles in all formulas contained functional groups such as alcohol, alkene, and amide.